Conceptualizing Business Process Violations - Dunzer, Sebastian; Ließmann, Annina; Stierle, Matthias; Matzner, Martin (CEUR Workshop Proceedings, 2024)
Process analysts seek to gain insights into process execution to continuously improve their business processes. Business process deviation analysis can prove useful in identifying process improvements. However, differentiating between relevant and irrelevant deviations poses challenges. This is due to commercial process mining software flagging a high number of process instances as deviations from process definitions (e.g., process models). Against this background, we define and conceptualize business process violations that indicate undesired behavior. This paper defines business process violations based on regulatory business process compliance. Furthermore, this paper conveys a conceptual model connecting business process violations, the process definition they violate, and their organizational setting. We structure these components in ten dimensions of business process violations. The conceptual model and dimensions were developed and evaluated based on real-world examples provided by a German software vendor. Our conceptualization provides the vocabulary and raises awareness to discuss deviations’ important aspects that delineate violations
Keywords: business process deviations; business process violation; process analysis; conformance; compliance